2010
DOI: 10.1098/rstb.2009.0311
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation with drift: a spatio-temporal genetic analysis of Galápagos mockingbird populations (Mimusspp.)

Abstract: Small and isolated island populations provide ideal systems to study the effects of limited population size, genetic drift and gene flow on genetic diversity. We assessed genetic diversity within and differentiation among 19 mockingbird populations on 15 Galápagos islands, covering all four endemic species, using 16 microsatellite loci. We tested for signs of drift and gene flow, and used historic specimens to assess genetic change over the last century and to estimate effective population sizes. Within-popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 49 publications
4
82
1
Order By: Relevance
“…In this manner several studies demonstrated a decrease of genetic diversity or an increase in genetic differentiation (e.g. refs 6,13,14). For instance, Athrey et al 15.…”
mentioning
confidence: 85%
“…In this manner several studies demonstrated a decrease of genetic diversity or an increase in genetic differentiation (e.g. refs 6,13,14). For instance, Athrey et al 15.…”
mentioning
confidence: 85%
“…In general, larger populations tend to be more genetically diverse (Fig. 1, arrow 4) (Kimura and Crow, 1964;Frankham, 2005a;Hoeck et al, 2010).…”
Section: Areamentioning
confidence: 97%
“…In general, larger populations tend to be more genetically diverse (Fig. 1, arrow 4) Frankham, 2005a;Hoeck et al, 2010).…”
Section: Areamentioning
confidence: 99%